2002
DOI: 10.1152/ajpgi.00291.2001
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of chloride secretion by baicalein in isolated rat distal colon

Abstract: The effect of baicalein on mucosal ion transport in the rat distal colon was investigated in Ussing chambers. Mucosal addition of baicalein (1–100 μM) elicited a concentration-dependent short-circuit current ( I sc) response. The increase in I sc was mainly due to Cl−secretion. The presence of mucosal indomethacin (10 μM) significantly reduced both the basal and subsequent baicalein-evoked I sc responses. The baicalein-induced I sc were inhibited by mucosal application of diphenylamine-2-carboxylic acid (100 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…It is noteworthy that Rut-induced I SC response is restored by the increase in intracellular cAMP level with an adenylate cyclase stimulator forskolin in the presence of indomethacin. The similar result was reported in rat colonic mucosa treated with baicalein (Ko et al, 2002). Determination of PGE 2 with enzyme-linked immunosorbent assay showed that a large part of Rut-mediated stimulation of Cl Ϫ secretion was occurred through prostaglandins release and synthesis mostly via activation of E-prostanoid receptors.…”
Section: Discussionsupporting
confidence: 85%
“…It is noteworthy that Rut-induced I SC response is restored by the increase in intracellular cAMP level with an adenylate cyclase stimulator forskolin in the presence of indomethacin. The similar result was reported in rat colonic mucosa treated with baicalein (Ko et al, 2002). Determination of PGE 2 with enzyme-linked immunosorbent assay showed that a large part of Rut-mediated stimulation of Cl Ϫ secretion was occurred through prostaglandins release and synthesis mostly via activation of E-prostanoid receptors.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, pretreatment with the loop diuretic bumetanide completely inhibited the barakol-stimulated Isc. All of these findings were consistent with stimulation of transepithelial Cl Ϫ secretion in human and rat colon (Dharmsathaphorn et al, 1985;Ko et al, 2002;Kunzelman and Mall, 2002). The finding that the increase in Isc by barakol was not affected by the presence of the Na ϩ channel blocker amiloride indicates that barakol did not stimulate electrogenic Na ϩ absorption.…”
Section: Discussionsupporting
confidence: 75%
“…Our finding was consistent with Cl Ϫ secretion induced by other plant-derived bioactive compounds, especially flavonoid baicalein. Baicalein has been shown to stimulate Cl Ϫ secretion across rat colonic epithelium by the activation of the cAMP-dependent apical Cl Ϫ channel and the basolateral K ϩ channels (Ko et al, 2002). From studies in human colonic cancer cells (T84 cells), baicalein was found to potentiate the Ca 2ϩ -mediated Cl Ϫ secretion via an accumulation of cAMP and activation of protein kinase A activity (Yue et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other known flavonoids, e.g., flavopiridol, genistein and apigenin, are either direct chloride secretagogues at high doses or potentiate responses to other stimuli at low doses in Calu-3 cells (26), T 84 colonic epithelial cells (27 -30) and in rat distal colon (31,32).…”
Section: Discussionmentioning
confidence: 99%